HUBUNGAN KUALITAS DAN KUANTITAS TIDUR DENGAN SIX-MINUTE WALK TEST PADA DEWASA MUDA DAN DEWASA TUA DI JAKARTA - Nadela Nadela; Denio Adrianus Ridjab; Dwi Jani Juliawati (Bahasa Indonesia, 2020)
Introduction: The general population often experiences lack of sleep and has poor sleep quality. Both can affect many things to the body, one is physical functional capacity. Physical functional capacity can be measured using a six-minute walk test (6MWT). Many studies have discussed about 6MW, however, none of the studies have specifically found its association with quality and quantity of sleep in young and older adults in Jakarta.Methods: This research is a descriptive-analytical cross-sectional study conducted on two groups, young and older adults. Data were collected from demographic questionnaires, Pittsburgh Sleep Quality Index (PSQI), and a six-minute walk test, which was directly measured. Bivariate analysis was conducted using Chi-square and independent T-test.Results: 62,5% of 40 young adults have poor sleep quality, while for older adults, only 26,7%. There are 67,5% of young adults that have inadequate sleep while for older adults, only 48,9%. Based on observation in 39 older adults, 57,9% walking distance of male older adults and 65% walking distance of female older adults were normal. In young male and female adults, normal walking distance was found in 50% and 44,4%, respectively. The bivariate analysis results showed a significant positive association between quality of sleep and 6MWT (p=0,03). There is no significant association between the quantity of sleep and 6MWT (p=0,797).Conclusion: Older adults have a higher number of good sleep quality and adequate sleep, a normal range of distance walked, and a farther mean distance walked than the young adults. There is a positive association between sleep quality and the 6MWT in both groups. A six-minute walk test needs to be considered more often as a measurement tool in evaluating sleep quality and quantity and its effect on physical function.